Sonography of the chest wall: A pictorial essay. Issue 9 (12th August 2015) - Lee, Ryan Ka Lok; Griffith, James Francis; Ng, Alex Wing Hung; Sitt, Jacqueline Ching Man
ABSTRACT Ultrasound (US) is increasingly being used as the first‐line imaging modality for investigating the chest wall for soft tissue and bony lesions. This article describes the technique used for the US examination, the relevant chest‐wall anatomy, and the appearances on US scanning of pathologic entities either unique to or common in the region of the chest wall. © 2015 Wiley Periodicals, Inc. J Clin Ultrasound43:525–537, 2015